2020
DOI: 10.2188/jea.je20200226
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Marginal Structural Models for Time-Varying Exposures: Pitfalls and Tips

Abstract: Epidemiologists are increasingly encountering complex longitudinal data, in which exposures and their confounders vary during follow-up. When a prior exposure affects the confounders of the subsequent exposures, estimating the effects of the time-varying exposures requires special statistical techniques, possibly with structural (ie, counterfactual) models for targeted effects, even if all confounders are accurately measured. Among the methods used to estimate such effects, which can be cast as a marginal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 82 publications
(206 reference statements)
2
22
0
Order By: Relevance
“…This approach has been used extensively within pharmacoepidemiology and is conceptually identical to a marginal structural model. 15 , 22 , 31 , 32 , 33 , 34 For a nontechnical summary, as well as a detailed, formal discussion of the method and a directed acyclic graph, see eFigure 1 in the Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been used extensively within pharmacoepidemiology and is conceptually identical to a marginal structural model. 15 , 22 , 31 , 32 , 33 , 34 For a nontechnical summary, as well as a detailed, formal discussion of the method and a directed acyclic graph, see eFigure 1 in the Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…presence of time-varying confounding. 21,45 Conventional analytic approaches, including other PS methods, fail to estimate the effects of a time-varying exposure when prior exposure affects confounders of subsequent exposure. 46 Comparison of PSM and IPW…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 99%
“…Lastly, IPW can be expanded to causal inference for a time-varying exposure in the presence of time-varying confounding. 21 , 45 Conventional analytic approaches, including other PS methods, fail to estimate the effects of a time-varying exposure when prior exposure affects confounders of subsequent exposure. 46 …”
Section: Pitfalls and Tipsmentioning
confidence: 99%
“…The MSM was originally developed as a methodology for post‐hoc adjusting of the confounding covariates in epidemiological studies where randomization may not be available. However, recent studies demonstrated that the method can help to interpret the data from controlled, randomized clinical trials 19 . For well controlled clinical trials with subsequent therapies, the implementation of the MSM can be significantly simplified under certain situations, for example, analysis with a point‐treatment subsequent therapy, because most of the fixed nuisance covariates can be controlled through randomization and the subsequent therapy may be the only confounder that cannot be balanced at initial randomization.…”
Section: Discussionmentioning
confidence: 99%